Physicochemical Properties of Torrefied and Pyrolyzed Food Waste Biochars as Fuel: A Pilot-Scale Study - Kwang-Ho Ahn; Dong-Chul Shin; Jinhong Jung; Yoonah Jeong; Ye-Eun Lee; I-Tae Kim (Energies, 2022)
Food waste is an important constituent of municipal solid waste, and research has been conducted to develop various methods for treating food waste and recycling it (e.g., fuel, landfilling, composting, conversion into animal feed, drying, and carbonization). Among these, the drying and carbonization techniques can change food waste into fuel; however, they need more energy than fermentation and anaerobic digestion procedures. In this study, we investigated the physicochemical properties of food waste biochar produced under torrefaction (270 °C) and pyrolysis (450 °C) conditions to establish its applicability as fuel by comparing temperatures, residence times, and conditions before and after demineralization. The higher heating value increased after the demineralization process under both temperature conditions (270 °C and 450 °C), and the chlorine level was lower at 270 °C temperature demineralization than at 450 °C. During the demineralization process, Na and K were better removed than Ca and Mg. Additionally, Cr, Hg, Cd, and Pb levels were lower than those according to the European Union and Korean domestic bio-SRF recovered fuel criteria, confirming the applicability of biochar as fuel.